The Development of Alcoholic Fermented Beverages Utilizing Plums with the Application of Innovative Beverage Fermentation Technology - Williams, G.; van Wyk, J.; Hansmann, C. (South African Journal of Enology and Viticulture, 2016)
The adaptation of existing technologies toward producing a white wine style alcoholic fermented plum beverage was undertaken. The Independent Variables (ID) were yeast strains (Saccharomyces cerevisiae VIN13 and Saccharomyces bayanus N96), with formulations containing various percentage pulp concentrations at (40%, 50% and 60%). The Dependent Variables (DV) constituted key quality parameters for white wines, namely %methanol, %ethanol, titratable acidity (TA), objective colour, total soluble solids (TDS), pH and sensory profile were measured. %Methanol was not detected in the samples, %ethanol, TA, colour, TDS and pH were within the range typical for white wine. The overall sensorial profile of the beverage samples, fruity aroma and sweet associated aroma were rated significantly higher as the pulp concentration increased from 40% to 50% (p < 0.05). Exhibiting comparable sensory attributes namely fruity aroma, sweet-associated aroma, yeasty aroma, sweet taste, sour taste, bitter taste, astringency and fruity flavour, that was typically associated with white wines (Sokolowsky et al., 2015). The results showed that existing technology can be adapted to produce an alcoholic fermented plum beverage of which the key quality parameters and attributes are comparable to white wines.